Passive solar floor heating in buildings utilizing integrated solar flat plate collector heat - Aresti, Lazaros; Christodoulides, Paul; Panayiotou, Gregoris; Theophanous, Elisavet; Kalogirou, Soteris A.; Florides, Georgios A. (My University, 2017)
Floor heating systems provide a comfortable indoor environment because they allow heat to flow slowly in a natural way from the floor upwards. In this way the occupants feel hotter on the feet and cooler on the head enjoying the indoor environment. To this contributes the temperature uniformity over the entire floor. Thermal mass integrated to the floor can act as a thermal reservoir that can store the solar gains of the day and, in this way cover the heating needs of the building under certain climate conditions. In this study we examine the use of the foundation concrete in new buildings as a storing material, where the heat gains of a flat plate collector array οn the south wall are driven and accumulated. As a first step a model building, typically insulated and with walls facing the four cardinal points, was chosen for the study. The south wall area was assumed to be covered with Integrated Solar Flat Plate Collectors and water circulated with a pump between the collectors and the foundation concrete when its temperature exceeded 40°C. A simulation model was built in TRNSYS with the above scenario and hourly results of the collected solar energy and building thermal load were calculated for the climatic conditions of Limassol, Cyprus. The hourly results of TRNSYS were then used as input for a simulation in COMSOL Multiphysics. The solar energy collected was directed for storing in the foundation concrete. After an initial time priming, the foundation’s temperature was raised enough in order to be able to provide the daily heating load of the building. A part of the daily solar energy collected with the collector facade on the south wall, was also directed into the foundation for replenishing the lost energy. The simulations then were engaged in examining the effect of various parameters, like the thickness of the concrete, the amount of heat available and that which is stored, as well as the controlling technique. The results show that in the climatic conditions of the area considered here, the system chosen can cover completely the heat requirements of the building and provide comfortable conditions for the occupants during winter.
Keywords: Floor heating systems; Model building